Human-made corals for marine habitats: Design optimization and additive manufacturing. (December 2021) - Lin, S; Bao, DW; Xiong, CW; Fang, J; An, HW; Sun, ZZ; Xie, YM; Zhou, SW
Highlights: We designed the human-made corals by minimizing a carbon-solidification-related objective function and considering the morphological characteristics of corals. We developed a surface mapping method to dent the surface of optimized structures homogeneously. We prototyped the designs by additive manufacturing with biologically compatible magnesium and prototyped photosensitive material to test their capability to replace natural corals. Abstract: This paper presents an optimization method to systematically design human-made corals using the technique of solid isotropic material with the penalization. In optimization, we minimized the squared norm of the carbon gradient and considered the volume constraint and the length constraint. We homogeneously dented optimization results using a surface mapping method to provide shelters for polyps, which widely exist in natural corals like the anthocyanins. A computational fluid dynamics investigation based on the lattice Boltzmann method illustrated that the branches of the optimized configuration could shield polyps from ocean currents and afford sufficient nutrition. Eventually, we prototyped samples by digital light processing printer with an optimum mixture ratio of biologically compatible calcium carbonate and photosensitive material. Examples show the tropism of marine organisms in human-made corals is akin to the natural ones. The proposed method allows designing human-made corals and is crucial for environmental remediation.